Mengembangkan Strategi Bisnis di Era Transformasi Digital - Dwi Robiul Rochmawati; Hani Hatimatunnisani; Mira Veranita (Coopetition : Jurnal Ilmiah Manajemen, 2023)
As contemporary organizations go through computerized change, the job of a practical methodology turns out to be vital for any organization. There are different significant perspectives to zero in on while fostering a computerized business system: specifically, expanding the extent of business tasks as well as carrying out the most recent IT answers for make this procedure a long haul "improvement" plan expected to keep up with the feasibility of the organization, execution and add to the accomplishment of the Sustainable Development Goals (SDGs). The reason for this article is to examine the improvement of effective business techniques in the computerized time. The technique utilized in this examination is a subjective illustrative strategy. The consequences of this conversation show that in the age of the "new economy" and the computerized change that goes with it, creative advanced business systems in view of modern IT arrangements and lined up with the SDGs are an extraordinary chance for organizations to stray from contenders and gain upper hand.